2021
DOI: 10.1108/ijse-01-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and environmental impacts of bridge construction: evidence from the Khan Jahan Ali Bridge, Khulna, Bangladesh

Abstract: PurposeKhan Jahan Ali (KJA) Bridge was constructed to promote industrial and commercial activity and improve economic and employment activity for local people. This study assessed the post-socioeconomic and environmental impacts of KJA Bridge on the inhabitants living adjacent to 2 Km from the bridge. As there is a slum adjacent to the bridge, the bridge has impacted much on the improvement of the social economic condition and lifestyle of the slum people.Design/methodology/approachThe study approached a quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Prior investigations carried out by Islam et al and Hasan et al during the beginning planning stage of this project also confirmed all these detrimental effects [ 1 , 8 ]. Additionally, the results of this study are consistent with recent EIA studies performed on the Khan Jahan Ali Bridge [ 4 ], Padma Multipurpose Bridge [ 5 ], Mymensingh Kewatkhali Bridge over the Old Brahmaputra River [ 49 ], Galachipa Bridge [ 7 ], Payra Bridge [ 14 ], Kashil Bridge over the Jhinai River at Tangail [ 58 ]. Furthermore, a recent study discovered that the Dharla Bridge's construction had several impacts on the hydrological and morphological features of the Dharla River [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Prior investigations carried out by Islam et al and Hasan et al during the beginning planning stage of this project also confirmed all these detrimental effects [ 1 , 8 ]. Additionally, the results of this study are consistent with recent EIA studies performed on the Khan Jahan Ali Bridge [ 4 ], Padma Multipurpose Bridge [ 5 ], Mymensingh Kewatkhali Bridge over the Old Brahmaputra River [ 49 ], Galachipa Bridge [ 7 ], Payra Bridge [ 14 ], Kashil Bridge over the Jhinai River at Tangail [ 58 ]. Furthermore, a recent study discovered that the Dharla Bridge's construction had several impacts on the hydrological and morphological features of the Dharla River [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…All the development activities like bridge construction must have some potentially negative impacts on the surrounding environmental components though they are built to benefit humankind by making the communication system faster and easily assessable [ 3 , 4 , 15 , 37 , 41 , 57 ]. According to this study, the proposed Boga Bridge will have several negative impacts on the surrounding environment such as loss of agricultural land and production, loss of aquatic habitat, extinction of endangered species, degradation of water, air, and soil quality, a decline of ecosystem health, loss of flora & fauna diversity, change in river flow, and sedimentation, etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations